BERBAGI PRAKTIK BAIK DALAM BUKTI KARYA LUARAN IN HOUSE TRAINING SEBAGAI MANIFESTASI TAHUN PRAEDICARE TIM SEKOLAH YAYASAN SANTO DOMINIKUS - Winarti, Eny; Hadiyanti, Agnes Herlina Dwi (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2024)
One of the works of the Saint Dominic Sister is education. As Indonesian education is shifting in the paradigm, the foundation feels the urgency to equip the education team with the ability to contribute to the Indonesian education trend without losing sight of its vision and mission. One of the Indonesian education trends for teachers is the use of Platform Indonesian Mengajar (PMM - Indonesian Teaching Platform) in which the teachers are expected to take part in developing their portfolio through the platform. By the foundation, this platform is deemed to be in line with the praedicare year I (2024-2025) in which the foundation focuses on making a public declaration. In the effort to announce good practices, preliminary data indicated that few of the school team, who are expected to be role models for other teachers, have actively contributed to PMM. A deeper analysis revealed that the foundation needed to facilitate those teachers to be familiar with the application. To deal with this challenge, a one-day workshop on how to upload the portfolio and what content to be uploaded on the PMM was conducted. The results of the workshop were that all school team in YSD schools were successfully upload their portfolio.